New era, new GOALs: cardiovascular screening and lipid management in cystic fibrosis - Katherine A. Despotes; Agathe S. Ceppe; Jennifer L. Goralski; Scott H. Donaldson (Therapeutic Advances in Respiratory Disease)
Background: Cardiovascular disease (CVD) risks are increasing in people with cystic fibrosis (pwCF). While cholesterol levels were historically low in pwCF, higher levels after initiating highly effective modulator therapy (HEMT) have been reported. Mechanisms are unclear and there is little guidance on screening. Objectives: To evaluate serum lipid changes at multiple timepoints after ivacaftor initiation, and to assess current screening practices for CVD risk factors among CF providers. Design: This was a post-hoc correlative analysis of prospectively collected clinical data and serum samples from the GOAL cohort study. Cross-sectional survey methodology was also employed. Methods: We evaluated serum lipids (total cholesterol (TC), low-density lipoprotein (LDL), and high-density lipoprotein (HDL)) at baseline, 3- and 18 months after ivacaftor initiation using samples from the GOAL study biorepository. We also surveyed CF providers across the United States on their CVD risk screening practices. Results: Fifty GOAL participants’ samples were analyzed. Using the repeated measures model, TC significantly varied by visit ( p  = 0.004), driven by a significant increase from baseline at 3 months (mean difference 9.4 mg/dL). This difference diminished by 18 months. BMI was a significant covariate for TC. No significant differences by visit were detected in LDL or HDL. Seventy-five respondents participated in the survey (response rate 5.6%; 41 adult providers, 18 pediatric providers, and 10 providers caring for both) with 67% reporting no lipid screening policy existed in their center. In the past year, 29% of adult providers prescribed lipid-lowering therapy, 54% started anti-hypertensive medications, and 48% initiated ischemic cardiac evaluations for pwCF. Conclusion: TC significantly increased within 3 months of initiating ivacaftor, but subsequently diminished toward baseline by 18 months. Lipid screening practices among CF providers were variable and providers are increasingly being confronted with managing CVD risk factors. Partnering with primary care providers is likely to become increasingly important in CF care models.